Changes in objectively measured sleep among internationally adopted children in 1-year follow-up during the first years in new families - Heikkilä, Anna-Riitta; Lapinleimu, Helena; Virtanen, Irina; Rönnlund, Hanni; Raaska, Hanna; Elovainio, Marko (Frontiers in Pediatrics, 2022)
Background: Psychosocial risks and environmental changes experienced by internationally adopted children may predict sleep problems, which are incidentally among the main concerns of adoptive parents. Several questionnaire studies have found sleep of internationally adopted children to be problematic, but none of those used an objective measure in a controlled study. Objective: To determine whether the objectively recorded sleep of internationally adopted children is worse than their controls who are living with their biological parents. Methods: To this case-control part of the Finnish Adoption Study, we recruited children who were adopted internationally to Finland between October 2012 and December 2016. Simultaneously, control children were recruited from 16 daycare centers. To assess sleep in children, actigraphy recordings were made twice, one year apart, between December 2013 and April 2018. In the adopted group, the first assessment took place ten months after they had arrived in their families. The associations between adoption status and sleep parameters were analyzed using linear mixed modelling and adjusted for multiple potential confounders, including child age. Results: Seventy-eight internationally adopted children (boys 64%) aged 1 to 7 years and 99 controls (boys 53%) aged 2 to 6 years attended the first sleep recording. The recordings showed that the internationally adopted children slept longer (B = 0.48, 95% CI 0.23 to 0.73, P<0.001) than the controls. There were no significant differences in sleep fragmentation or sleep efficiency between the groups. During the one-year follow-up, the sleep patterns of the adopted children approached those of the controls. Conclusions: The internationally adopted children spent more time in bed and slept more than their control children in both recordings. However, their sleep patterns were not very different from those of their peers and the differences appeared to vanish during the first years in their new family.